Anatomy of the Homicide Rise. Issue 3 (August 2019) - Rosenfeld, Richard; Fox, James Alan
After declining for over two decades, homicides in the United States rose sharply in 2015 and 2016. We dissect the homicide rise by characteristics of the victims, offenders, and incidents and devote special attention to the similarities and differences in homicide growth by race. The results indicate that the upturn was demographically and geographically pervasive and encompassed multiple event circumstances. Regardless of whether the 2014 to 2016 homicide spike was a short-run aberration in the long-term crime drop or augurs an extended increase in lethal violence, it should be explained. We offer some general directions for explanatory research on the homicide rise.